Avaliação do potencial do material de sorgo Sacarino ADV 2010 para produção de etanol e silagem, em dois cortes, na região oeste do Paraná - Gerke, Lincoln Villi (2015)
The sorghum was investigated as a food source to replace corn and alternative to sugar cane for ethanol production. Experimental in the State University of Paraná- UNIOESTE West station in Rondon-PR, with the hybrid ADV 2010, which was ensiled and processed with the same equipment already used in the processing of corn and sugarcane, produced a quantity of biomass that exceeded the volume of 165,000 kg of fresh weight per hectare in two sections with an ethanol production of 1,035 liters per hectare in the 1st section and 695 liters per hectare in regrowth, resulting in a cost of R$ 1.26 per liter produced in a rural property. The chemical composition of silage dry matter, acid detergent fiber, neutral detergent fiber, ash and crude protein were relevant in the silage. The results showed that there is viability in producing ethanol from sweet sorghum in rural properties, an additional investment. The economic potential of the material, addition of ethanol and silage extends to the biomass, which can be used for other purposes, and food, can be dried and incorporated into animal feed (fiber) in digesters supply or production steam boilers.